2019
DOI: 10.1097/ijg.0000000000001179
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related Performance and Quality of Life of Patients With Rapid Glaucoma Progression

Abstract: Purpose: The purpose of this study was to determine how clinical measures, performance-based measures and subjective assessments of vision-related quality of life (VRQoL) are affected in patients with rapid glaucoma progression. Methods: Prospective longitudinal study that included 153 patients diagnosed with moderate glaucoma. A subset of patients that presented with rapid glaucoma progression (n=22), defined as visual field (VF) mean deviation (MD) lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
5
0
3
Order By: Relevance
“… 22 Establishing the rate of progression in a timely manner is vital to detect which patients are at risk of developing visual impairment early enough to maintain patients’ quality of life. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Establishing the rate of progression in a timely manner is vital to detect which patients are at risk of developing visual impairment early enough to maintain patients’ quality of life. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…Vision-related quality of life (VRQoL) may be defined as a person's satisfaction with their visual function and its effect on daily life, and this may be negatively impacted by glaucoma-related visual impairment [5] . Studies have found associations between healthrelated or VRQoL scores and multiple factors in glaucoma patients including visual acuity [6][7][8][9][10][11] , visual field status [6][7][8]10,[12][13][14][15][16] , optical coherence tomography [17] , visual symptoms [18] , rate of glaucoma progression [19] , and socio-economic factors such as age, marital status, literacy, and place of residence [20] . The number of QoL studies in glaucoma has increased since the early 1990's however, there are still fewer QoL studies in glaucoma than in other disabling chronic diseases [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Ainda que a farmacoterapia ofereça a forma menos invasiva do tratamento, os pacientes podem experimentar eventos adversos que reduzem a VRQoL ou comprometer os resultados em saúde (15,32,33) . Devido ao curso crônico e progressivo da doença, geralmente, os pacientes mantêm o tratamento farmacoterápico diário, com a intensidade do tratamento aumentando de acordo com a progressão da doença (15) .…”
Section: Introductionunclassified
“…Dessa forma, as medidas baseadas no desempenho ou performance, que são menos comuns em ensaios clínicos, podem fornecer uma avaliação objetiva de como o glaucoma afeta a VRQoL dos pacientes. Entretanto, são poucos os estudos que investigaram o impacto do glaucoma em medidas baseadas no desempenho (33) . Ramulu et al (2009) (58) apontaram diminuição na velocidade da leitura e seu comprometimento com a perda bilateral do CV.…”
Section: Introductionunclassified
See 1 more Smart Citation